2019
DOI: 10.2139/ssrn.3466373
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of International Investment Income in Emerging Market Economies

Abstract: Version: October 2019Forthcoming in the Review of International EconomicsWe investigate international investment income flows in 26 emerging market countries during the period of 1998-2015. Net investment income registered a deficit for this group of countries of between 2-3% of GDP during this period. This deficit has been dominated by payments on foreign direct investment liabilities, which is consistent with the change in the composition of the external liabilities of these countries. Our results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…While banks have mostly benefited from technological advancements, some have experienced the negative impact of technology. There is a positive relationship between net investment income and net financial asset (Joyce, 2019;Aberola et al, 2020;Hiattori et al, 2023). Every area of the banking sector, from IT and security to operations and team relations, has felt the corrosive effects of technology on corporate communication.…”
Section: Discussionmentioning
confidence: 99%
“…While banks have mostly benefited from technological advancements, some have experienced the negative impact of technology. There is a positive relationship between net investment income and net financial asset (Joyce, 2019;Aberola et al, 2020;Hiattori et al, 2023). Every area of the banking sector, from IT and security to operations and team relations, has felt the corrosive effects of technology on corporate communication.…”
Section: Discussionmentioning
confidence: 99%
“…The international income surpluses recorded by many advanced economies are matched by deficits in emerging market countries. Joyce (2021) found that payments on FDI liabilities are largely responsible for the net investment income deficits recorded by these countries. Zélity (2020) has examined the welfare impact of FDI profits in the four Visegrád countries.…”
Section: Literature Reviewmentioning
confidence: 99%